Fuzzy System To Predict Student Performance Levels Using Formative Evaluation - Thiam, Yeoh Eng (2008)
This thesis describes the research on the problem of assessing student performance using formative evaluations in some Software Engineering courses. In these courses, it was difficult to assess the student performance levels in order to predict their performance in the final examination of the course. The purpose of this research is to investigate the application of fuzzy logic to improve the prediction of student performance levels in the final examination.